ORGANIZATIONAL COMMUNICATION AS A FOUNDATION OF BUSINESS EFFECTIVENESS: A CONCEPTUAL REVIEW IN THE CONTEXT OF OFFLINE AND ONLINE MARKETING - Lili Karmela Fitriani; Diar Mutiarawati; Derik Rizki Pangestu (CV. Radja Publika, 2026)
Communication is a fundamental process that determines the success of coordination, motivation, and decision-making within organizations and business activities. This article conceptually examines the process, direction, media, barriers, and cross-cultural dimensions of organizational communication based on Robbins and Judge's framework, and relates them to marketing communication practices in offline and online business contexts. A descriptive-qualitative library research method was used, reviewing core organizational behavior literature alongside recent digital marketing journals. The findings show that the effectiveness of organizational communication is strongly influenced by the fit between channel richness and message ambiguity, an understanding of psychological and cultural barriers, and adaptability to digital channels in customer interaction. As a result, business actors, whether operating conventionally (offline) or through social media and e-commerce (online), need to design communication strategies aligned with audience characteristics and message nature to build productive working and customer relationships.